Purchase behavior of retailer own brand label products - Tunku Nur Atikhah Tunku Abaidah, Nor Azila Mohd Noor, (Opción, 2019)
This study was conducted to examine the influences of consumers’ perceptions on perceived value, perceived quality, perceived low price and store image on purchase behavior of retailers' own-brand products. The study was conducted at three main retail stores involving 130 respondents. Mall intercept survey method was used as a data collection method. Using Smart PLS, data were analyzed. The results showed that perceived quality, perceived low price and store image were positively related to the purchase behavior of retailers' own brands. In conclusion, the perceived value was discovered to be non- significantly related to purchase behavior of retailers' own brands.